Efek Multimedia Pembelajaran pada Kemampuan Siswa Menjawab Soal Analisis Energi pada Perubahan Wujud Air: Sebuah Tinjauan pada Siswa Kelas X Sman 3 Mataram - imran imran; Ahmad Harjono; Gunawan Gunawan (Department of Physics Education, Universitas Mataram, 2015)
The purpose of this study was to determine the effect learning multimedia on studentsÃ¢â¬â¢ ability to answer problems on heat concepts, especially in the analysis of the of energy in water form change. The study was conducted in class X of SMAN 3 Mataram. Total number of sample was 80 students, divided into two classes: 42 students in Experimental class taught using interactive learningmultimedia, and 38 student in control class taught without interactive learningmultimedia. Data were analyzed using ANOVA. The results showed that the ability of the students working on the energy analysis is better in the experimental class than the control class (ÃÂ± = 0.05; sig = 0.03).